2012
DOI: 10.1210/jc.2012-2043
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in Endocrine Disorders: Biological, Clinical, and Nonclinical Factors—An Endocrine Society Scientific Statement

Abstract: Several themes emerged in the statement, including a need for basic science, population-based, translational and health services studies to explore underlying mechanisms contributing to endocrine health disparities. Compared to non-Hispanic whites, non-Hispanic blacks have worse outcomes and higher mortality from certain disorders despite having a lower (e.g. macrovascular complications of diabetes mellitus and osteoporotic fractures) or similar (e.g. thyroid cancer) incidence of these disorders. Obesity is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
288
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 344 publications
(297 citation statements)
references
References 404 publications
(419 reference statements)
5
288
3
1
Order By: Relevance
“…Married individuals are 1.21 times more likely to have undiagnosed DM compared to single individuals. Some finding suggest that time constrain when managing careers and family life among married couples may cause lack of opportunity and awareness for prevention practices (Golden et al, 2012). However, other study have suggested that single, divorced and widowed statuses increase the risk of developing DM (Poljičanin, T., Šekerija, M., Boras, Kolarić, Vuletić, & Metelko, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Married individuals are 1.21 times more likely to have undiagnosed DM compared to single individuals. Some finding suggest that time constrain when managing careers and family life among married couples may cause lack of opportunity and awareness for prevention practices (Golden et al, 2012). However, other study have suggested that single, divorced and widowed statuses increase the risk of developing DM (Poljičanin, T., Šekerija, M., Boras, Kolarić, Vuletić, & Metelko, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] In growing recognition of the failure of the metabolic syndrome to detect risk for cardiometabolic disease in African Americans, the 2012 Endocrine Society Position Statement on Health Disparities suggests moving away from the metabolic syndrome and focusing instead on blood pressure and degree of glycemia. 16 Due to the similarities that we have demonstrated between African Americans and African immigrants, the same approach should be applied to Africans. In an earlier investigation, we found that metabolic syndrome performed poorly in predicting cardiometabolic risk in Africans.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples for the measurement of glucose and insulin levels were obtained at -10, -5, -1, 1, 2, 3,4,5,6,7,8,10,12,14,16,19,22,23,24,25,27,30,40,50,60,70,80,90, 100, 120, 150, and 180 min. IM-FSIGT data were used to calculate the insulin sensitivity index (S I ) and acute insulin response to glucose (AIRg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortified foods represent the major dietary source of vitamin D (6) and more than one-half of the US population uses dietary supplements (7) . In addition, vitamin D is produced endogenously through exposure of skin to UV light, which stimulates conversion of the precursor 7-dehydrocholesterol to pre-vitamin D 3 that is rapidly converted to cholecalciferol (8) .…”
mentioning
confidence: 99%